Argus. - (:unkn) unknown (Renegal, W., 1780)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820; Britannia (Symbolic character); Great Britain -- Relations -- Ireland; Irish -- Caricatures and cartoons